Ectopic Expression of OsDREB1G, a Member of the OsDREB1 Subfamily, Confers Cold Stress Tolerance in Rice - Moon, Seok-Jun; Min, Myung Ki; Kim, Jin-Ae; Kim, Dool Yi; Yoon, In Sun; Kwon, Taek Ryun; Byun, Myung Ok; Kim, Beom-Gi (Frontiers in Plant Science, 2019)
Plants adapt to adverse environmental conditions through physiological responses, such as induction of the abscisic acid signaling pathway, stomatal regulation, and root elongation. Altered gene expression is a major molecular response to adverse environmental conditions in plants. Several transcription factors function as master switches to induce the expression of stress-tolerance genes. To find out a master regulator for the cold stress tolerance in rice, we focused on functionally identifying DREB subfamily which plays important roles in cold stress tolerance of plants. Here, we characterized OsDREB1G (LOC_Os02g45450), a functionally unidentified member of the DREB1 subgroup. OsDREB1G is specifically induced under cold stress conditions among several abiotic stresses examined. This gene is dominantly expressed in leaf sheath, blade, node and root. Transgenic rice overexpressing this gene exhibited strong cold tolerance and growth retardation, like transgenic rice overexpressing other OsDREB1 genes. However, unlike these rice lines, transgenic rice overexpressing OsDREB1G did not exhibit significant increases in drought or salt tolerance. Cold-responsive genes were highly induced in transgenic rice overexpressing DREB1G compared to wild type. In addition, OsDREB1G overexpression directly induced the expression of a reporter gene fused to the promoters of cold-induced genes in rice protoplasts. Therefore, OsDREB1G is a typical CBF/DREB1 transcription factor that specifically functions in the cold stress response. Therefore, OsDREB1G could be useful for developing transgenic rice with enhanced cold-stress tolerance.